Stability testing of sustainable materials for photovoltaic application - Nizamov, Rustem (fi=Turun yliopisto|en=University of Turku|, 2025)
Sustainable materials hold great promise for photovoltaic and other photoresponsive applications; their long-term performance, however, is significantly affected by ultraviolet (UV)-induced degradation and other environmental stressors. This thesis investigates the stability and degradation mechanisms of various sustainable materials and devices—nanocellulose (NC)-based films, zinc oxide (ZnO)-coated textiles, dye-sensitized solar cells (DSSCs), and perovskite solar cells (PSCs)—under various conditions. A consistent, non-invasive, color-based method was used to assess degradation, providing insights into material performance and durability over time. The research on NC-based films targeted their optical performance, particularly their UV-shielding properties, achieved by incorporating sustainable additives like lignin and red onion (Allium cepa) extract. While bio-based UV filters have demonstrated promising initial results, their long-term effectiveness remains unexplored. To address this gap, extended aging tests were conducted to evaluate their capacity to provide sustained UV protection over time. This color-based assessment was also explored in photovoltaic devices, including DSSCs and PSCs, where color alterations were correlated with electrical performance changes. While color alteration and degradation occurred concurrently in PSCs, electrolyte color changes in DSSCs offered a predictive tool for degradation, potentially accelerating stability research. The study also investigated ZnO-coated textiles for their UV-blocking and photocatalytic self-cleaning capabilities. Furthermore, to address challenges in PSC research where substrate etching introduces variability, a tunable-design additivemanufactured holder was developed. The color-based technique, applied across these diverse studies, proved robust and cost-effective for tracking material changes and monitoring stability. Observed color alterations consistently served as an indicator of degradation, correlating with changes in optical and electrical properties across various materials. These findings contribute to advancing durable, eco-friendly materials and establishing scalable methods for stability assessment.